Organizational Culture, Management Accounting Information, Innovation Capability and SME Performance - Mitsalina Tantri; Andry Priharta; Siti Hamidah; Luqman Hakim; M. Nur A. Birton (Journal of Business and Behavioural Entrepreneurship, 2022)
In accordance with the theories of organizational culture, innovation diffusion and TAM, this study examines the relationship between organizational culture, management accounting information, innovation capability and company performance in small and medium enterprises (SMEs) in the city of South Tangerang. Data for the study were collected through a questionnaire survey of a sample of 160 top and middle level managers in SMEs. The results obtained reveal that organizational culture has a significant positive effect on company performance. In addition, the results show that the use of management accounting information and innovation capability has no significant effect on firm performance.